2017
DOI: 10.3390/ijms18061256
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Functional Characterization of a Hexokinase from the Oriental River Prawn Macrobrachium nipponense in Response to Hypoxia

Abstract: Metabolic adjustment to hypoxia in Macrobrachium nipponense (oriental river prawn) implies a shift to anaerobic metabolism. Hexokinase (HK) is a key glycolytic enzyme in prawns. The involvement of HK in the hypoxia inducible factors (HIFs) pathway is unclear in prawns. In this study, the full-length cDNA for HK (MnHK) was obtained from M. nipponense, and its properties were characterized. The full-length cDNA (2385 bp) with an open reading frame of 1350 bp, encoded a 450-amino acid protein. MnHK contained high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…This anaerobic backing was probably necessary as a consequence of the energetic demands involved in the compensatory mechanisms described. Sun et al (2017) reported an increase in hexokinase activity in M . nipponense and linked it to the expression of hypoxia‐inducible factors as a consequence of anaerobic metabolic energy demands.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This anaerobic backing was probably necessary as a consequence of the energetic demands involved in the compensatory mechanisms described. Sun et al (2017) reported an increase in hexokinase activity in M . nipponense and linked it to the expression of hypoxia‐inducible factors as a consequence of anaerobic metabolic energy demands.…”
Section: Discussionmentioning
confidence: 98%
“…The main compensatory responses were observed after the first 24 h of oxygen reduction, although high levels of oxy-haemocyanin were observed during the entire duration of the experiment. Similarly, short-term experiments (3 and 24 h) showed that Macrobrachium nipponense (De Haan, 1849) made metabolic adjustments via the anaerobic metabolism in hypoxia; these adjustments involved an increase in hexokinase, which is the initial enzyme of glycolysis (Sun et al, 2017). It was also observed that hexokinase activity was involved in the response triggered by hypoxia-inducible factors HIF-1α and β, and was key in the anaerobic pathways that allow the high metabolic activity observed during hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…A gene with hypoxia response elements (HRE) that is recognized by HIF as ENO has been, HK has also been studied widely [ 33 ]. Although the relationship between HK and HIF has been researched in previous studies by RNA inference technology [ 34 ], there is no research about the specific expression profile of HK in M. nipponense under hypoxia. It was clearly observed that Mn-HK increased after 6 h of hypoxia and then decreased ( Figure 7 E, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro synthesis of dsRNA was performed as previously described [49], and 120 healthy prawns (weight = 2.4 ± 0.6 g) were assigned to experimental and control groups in triplicate. The 60 prawns in the experimental group were injected with 4 μg/g body weight ATG4B dsRNA via the carapace pericardial cavity membrane [49]. Controls ( n = 60) were injected with an equal amount of dsEGFP dissolved in the injection buffer.…”
Section: Methodsmentioning
confidence: 99%